ASSOCIATION BETWEEN LIFE HABITS AND CARDIOVASCULAR RISK IN PEOPLE LIVING WITH HIV/AIDS - Marcela Antonini; Elizabete Santos Melo; Christefany Régia Braz Costa; Giselle Juliana de Jesus; Elucir Gir; Renata Karina Reis (Universidade Federal do Paraná, 2018)
Objective: To analyze the life habits and cardiovascular risk of people living with the human immunodeficiency virus, through sociodemographic, clinical and behavioral factors. Method: Cross-sectional quantitative study carried out in specialized services in the care of people living with the human immunodeficiency virus, from 2014 to 2016, in a municipality in the inland of the state of São Paulo - Brazil. The Framingham Risk Score was used to stratify cardiovas-cular risks. Results: Three hundred forty (340) individuals participated in the study. There was an association between cardiovascular risk and the variables gender (p = 0.003), age (p <0.001), education (p = 0.006), family history of hyper-tension (p = 0.026), diabetes (p = 0.003), myocardial infarction (p = 0.004) and stroke (p=0,003), time elapsed since HIV diagnosis (p <0.001) and time elapsed since the beginning of use of antiretrovirals (p = 0.003). Conclusion: The results revealed associations between cardiovascular risk and modifiable and non-modifiable risk factors for the occurrence of cardiovascular diseases in people living with HIV.